INTEGRASI PENDIDIKAN KARAKTER BERBASIS KURIKULUM CINTA PADA MATA PELAJARAN AKIDAH AKHLAK DI MTS MIFTAHUL ULUM PANGKALAN BALAI - Ismarani Junia Putri; Izzatuzzahroh; Saipul Annur; Afriantoni (STKIP Subang, 2026)
This study aims to analyze the integration of character education based on the “Curriculum of Love” into the teaching of Akidah Akhlak at MTs Miftahul Ulum Pangkalan Balai. Character education is a crucial aspect in shaping students’ personalities, particularly in addressing the challenges of moral decline in the modern era. The “Curriculum of Love,” as a humanistic approach, emphasizes the values of compassion, empathy, and exemplary behavior in the learning process. The method used was a literature review with a descriptive qualitative approach. The results of the study indicate that the integration of the love-based curriculum into Akidah Akhlak instruction can enhance the internalization of noble moral values, strengthen teacher-student relationships, and foster a religious character grounded in compassion.